2010
DOI: 10.1159/000319781
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Paricalcitol versus Cinacalcet for Secondary Hyperparathyroidism in Patients Receiving Hemodialysis

Abstract: Background/Aims: Parathyroidectomies are performed when medical therapy fails to control secondary hyperparathyroidism in hemodialysis patients. The objective of this study was to compare parathyroidectomy rates in secondary hyperparathyroidism patients treated with paricalcitol or cinacalcet. Methods: Retrospective cohort study using health insurance claims from January 2001 through June 2007 for adult hemodialysis patients who were new users of paricalcitol or cinacalcet. Subjects had a minimum of 12 months’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…The present analysis suggested that treatment strategies with cinacalcet, cinacalcet plus low-dose active vitamin D analogues and paricalcitol were superior to conventional therapy in dialysis patients with SHPT. In addition, consistent with previous observations (25,43), it was revealed that paricalcitol may be the most effective drug for controlling PTH and serum calcium. Previously, a retrospective cohort study suggested that patients receiving paricalcitol had a 74% lower parathyroidectomy incidence rates compared with patients receiving cinacalcet (43).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present analysis suggested that treatment strategies with cinacalcet, cinacalcet plus low-dose active vitamin D analogues and paricalcitol were superior to conventional therapy in dialysis patients with SHPT. In addition, consistent with previous observations (25,43), it was revealed that paricalcitol may be the most effective drug for controlling PTH and serum calcium. Previously, a retrospective cohort study suggested that patients receiving paricalcitol had a 74% lower parathyroidectomy incidence rates compared with patients receiving cinacalcet (43).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, consistent with previous observations (25,43), it was revealed that paricalcitol may be the most effective drug for controlling PTH and serum calcium. Previously, a retrospective cohort study suggested that patients receiving paricalcitol had a 74% lower parathyroidectomy incidence rates compared with patients receiving cinacalcet (43). Even with adjustment for comorbidities, gender, therapy time and other risk factors, the risk of parathyroidectomy was increased in the cinacalcet group compared with the paricalcitol group (43).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…FARO 2 study showed that paricalcitol administered intravenously significantly increased the number of patients at the target for the combined endpoint composed of PTH, calcium and phosphate ( P = 0.001), although the intravenous calcitriol and paricalcitol iv and cinacalcet combination groups weren't assessed due to the low patients number (2). In the retrospective study, Schumock et al (33) compared rates of surgical intervention (parathyreoidectomy) in secondary hyperparathyroidism patients treated with paricalcitol or cinacalcet. They found that long-term treatment with paricalcitol was connected with lower number of parathyroidectomies in comparison with the patients treated with cinacalcet.…”
Section: Discussionmentioning
confidence: 99%
“…These two latest criteria were set to ensure the continuity of care of the patients. The patients who met the criteria were likely to receive the treatment for asthma at the study site [14][15][16]. The index date for each patient was the first diagnosis date during the study period.…”
Section: Patients and Study Periodmentioning
confidence: 99%